The Treaties of Karlowitz, the Constantinople Agreement (1699–1700) and the initial phase of the Great Northern War - Piotrowski, Bernard (Balcanica Posnaniensia. Acta et studia, 2003)
The aim of this article is to present the political and diplomatic circumstances and actions taken by Sweden, Denmark and Russia just before the outbreak of the Great Northern War (1700–1721). The author focuses on the role of the Karlowice Treaties (1699) and the Russian-Turkish agreement in Constantinople (1700) as important factors enabling Russia to become actively involved in the conflict in the Baltic region. The analysis uses a historical-comparative method. Diplomatic documents and historiographical studies were used. The conclusion of peace with Turkey enabled Russia to turn towards the Baltic and paved the way for war with Sweden. Based on the sources, the author highlights the weakness of Swedish diplomatic initiatives, the erroneous strategic decisions of Charles XII, and the political foresight of Tsar Peter I.